Expression of Interleukin-1ß and Interleukin-8 in Oral Potentially Malignant Disorders and Carcinomas - Lopez-Labady, Jeaneth; Bologna-Molina, Ronell; Villarroel-Dorrego, Mariana (Frontiers in Oral Health, 2021)
Objective: To evaluate IL-1ß and 8 epithelial expression in potentially malignant disorders of the oral mucosa as malignant predictive markers. Study Design: 55 tissues embedded in paraffin, comprising 15 oral lichen planus (OLP) lesions, 15 leukoplakias, 15 oral squamous cell carcinomas (OSCC) and 10 samples of normal oral mucosa were included in the study. IL-1ß and 8 expressions were assessed by immunohistochemistry using antibodies anti-human IL-1ß human (sc-7884, Santa Cruz® H-153) and anti-human IL-8 (ab7747, abcam®). Number of positive cells was compared using Student´s t test. Any p value < 0.05 was considered statistically significant. Results: Nuclear and cytoplasmatic keratinocyte staining was positive for both cytokines in all study groups. However, a statistically significant decrease was observed within all cases compared to normal mucosa, both staining for IL-1β and 8. Moreover, IL-8 showed significant differences for OLP and leukoplakia, among them and compared to OSCC. Conclusions: Oral epithelial expression of IL-1β and 8 seems to decrease when malignant transformation of the oral mucosa increases.